ANALISIS SISTEM PENGENDALIAN INTERN TERHADAP SISTEM AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PT. JASA RAHARJA (PERSERO) KANTOR PERWAKILAN BOGOR - Putri, Susanti Eka; Setiawan, Ade Budi (Universitas Djuanda, 2016)
This research carry to know the internal control systemof cash in company BUMN (State Owned Company Engaged) in the sector of accident insurance servicesroad traffic, that is PT. Jasa Raharja (Persero) Representative Office Bogor at street Ahmad Yani Number 48 Bogor . This research to intend to know the internal control system of cash related receive of premium and expenses of policy that is to run in PT. Jasa Raharja (Persero) Representative Office Bogor. The internal control is something system and procedure applied by company management on order to save the company’s assets from action fraud, thief, intended or unintended errors, careless, or negligence officer, as well as to check the validity or accuracy and reliability of an enterprise accounting data, and aims to improve the efficiency of its operations, to support compliance policies predetermined by the company. This research to use descriptive analysis with approach qualitative. Output of research already carry have shown that internal control of cash on procedure receive premium and expenses policy in PT. Jasa Raharja (Persero) Representative Office Bogor already adequate and to run suitable the conditions set by the company. It is evidenced by the documents used, related parties in the process receive and expenses of cash of company, as well as process to run activity receive and expenses of cash, most have been in accordance with the Standard Operating Procedures (SOP) of company, as well as most of theInternal control of cash also complies with the elements of internal control.Keywords: Internal Control of Cash Receive and Expenses